Tradocratic Leadership Style and Its Imperative for African Development: Towards a Theory of Leadership for Africa - Osa , Ehiorobo Abraham (Unilag Journal of Humanities, 2019)
The paper examined the leadership dilemma faced by the African continent in its quest to make meaningful progress and development since independence from colonial Europe. After more than half a century of self-determination, many African countries are still in search of a leadership model that can lead their people out of excruciating poverty, bad governance by a privileged few, looting of the public treasury, political instability, economic crisis, infrastructural decay, non-functional educational systems, high crime rates, and opportunistically tyrannical leadership. It is noteworthy that African countries trying to practise the western democratic leadership style, as being practised in Europe and America, have had tremendous challenges as cultural differences were not considered in adopting such models. The tradocratic leadership style being proposed in this article combines the ideals of African traditional leadership styles, the traits theories, the Ubuntu philosophy and western democratic ideals into a truly African model of leadership that is culture and value-based. It is a conceptual study based on a comprehensive review of existing historical books and articles, management and leadership studies by previous authors. Conclusion drawn from the study indicated that the tradocratic leadership style, if adopted, could be the rescuing model that can transform Africa and place the continent on the path of development.